1984
DOI: 10.1148/radiology.151.1.6701299
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral CT findings in toxemia of pregnancy.

Abstract: Cerebral CT findings in two patients who had eclampsia are presented. Diffuse cerebral edema and basal ganglia involvement, which were previously undescribed to our knowledge, are exhibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…However, eclamptic fits in patients are asso ciated with cerebral edema and cerebral thrombosis [9]. Vasospasm and vasospasm-induced ischemia are well known to occur in eclampsia [8], In this study, we found clinical convulsions in all 7 pregnant and 2 nonpregnant rabbits after intravenous administration of variable doses (500 pmol/kg) of ET-l. High-voltage spikes, high-voltage fast and high-voltage slow waves in the EEG occurred in all the convulsive rabbits after ET-l administration.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…However, eclamptic fits in patients are asso ciated with cerebral edema and cerebral thrombosis [9]. Vasospasm and vasospasm-induced ischemia are well known to occur in eclampsia [8], In this study, we found clinical convulsions in all 7 pregnant and 2 nonpregnant rabbits after intravenous administration of variable doses (500 pmol/kg) of ET-l. High-voltage spikes, high-voltage fast and high-voltage slow waves in the EEG occurred in all the convulsive rabbits after ET-l administration.…”
Section: Discussionsupporting
confidence: 48%
“…In our pre vious study, we found a HELLP syndrome-like condition in rabbits with endothelin-1 (ET-1) injections [7], Vaso spasm and vasospasm-induced ischemia are well known to occur in eclampsia [8]. Patients with eclamptic fits were found to be associated with cerebral edema [9] and cere bral thrombosis. However, the exact cause of seizures and the disease process still have to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Eclampsia occurs as a complication of pregnancy with a reported incidence of only 0.05 per cent to 0.2 per cent [6], and the development of transient blindness as a neurologic symptom is an even more rare finding [7]. Cerebral edema has been a consistent finding in the CT reports of patients with eclampsia [8][9][10][11][12]. The presence of vasospasm with poor filling of peripheral vascular territories has also been angiographically proven during the acute episode in two patients [13] providing supportive evidence for the role of vasospasm in the production of neurologic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosed cerebral arterioles cause micro-infarcts and circumferential haemorrhage in the cerebral cortex [106]. Cerebral oedema has been demonstrated by CT scan [107], but was not found at autopsy in women dying with eclampsia [106]. Although generalised convulsions are usual, clinical manifestations depend on the site of ischaemia.…”
Section: Brainmentioning
confidence: 99%